2019
DOI: 10.1101/687954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Label-retention expansion microscopy

Abstract: Expansion microscopy (ExM) improves the resolution of fluorescence microscopy by physically expanding the sample embedded in a hydrogel 1-4 . Since its invention, ExM has been successfully applied to a wide range of cell, tissue and animal samples 2-9 . Still, fluorescence signal loss during polymerization and digestion limits molecular-scale imaging using ExM. Here we report the development of label-retention ExM (LR-ExM) with a set of trifunctional anchors that not only prevent signal loss but also enable hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…Indeed, our quantification in CH3 channel showed that the protein loss could reach 79% ( Fig. 1f), consistent with a recent fluorescence analysis 18 . With such a high protein content loss and an approximate 64-fold signal dilution due to 4-fold isotropic sample expansion, SRS signals are therefore diminished.…”
supporting
confidence: 91%
“…Indeed, our quantification in CH3 channel showed that the protein loss could reach 79% ( Fig. 1f), consistent with a recent fluorescence analysis 18 . With such a high protein content loss and an approximate 64-fold signal dilution due to 4-fold isotropic sample expansion, SRS signals are therefore diminished.…”
supporting
confidence: 91%
“…8 and 9) 34,35 our findings are highly relevant. Very recently 36,37 , trifunctional linkers have been introduced that are inert to polymerization, digestion and denaturation, and enable direct covalent linking of target molecules and functional groups to the hydrogel. Therefore, trifunctional linkers can retain a high number of labels and fluorescence molecules available for postexpansion imaging.…”
Section: Discussionmentioning
confidence: 99%
“…For larger volume reconstructions, ExM has been combined with lattice-light-sheet microscopy for high-throughput imaging of neural circuits including entire fly brains (Gao et al, 2019a; Figure 5J). To further increase image resolution, Ex-SIM (Cahoon et al, 2017;Halpern et al, 2017), Ex-STED (Gao et al, 2018), and Ex-STORM (Cang et al, 2016;Shi et al, 2019) have each combined physical expansion with optical superresolution imaging to achieve multiplicative increases in spatial resolution. By combining the advantages of single-molecule photoswitching and spatially-patterned excitation, MINFLUX achieves the highest resolution reported in far-field fluorescence imaging by using a central excitation minimum to localize individual molecules based on their minimal fluorescence emission (Balzarotti et al, 2017).…”
Section: Volumetric Super-resolution Imaging and Hybrid Methods For Imentioning
confidence: 99%